Mathematics
sweetsuites
2015-11-12 14:46:57
Solve the system of linear equations below. 2x + 3y = 2 x + 6y = 4 x = 0, y = 2 3 x = 2, y = - 2 3 x = 4 3 , y = 2 9 x = 4, y = -2
ANSWERS
georginaosae
2015-11-12 19:29:38

2x + 3y = 2 x + 6y = 4 ....multiply by -2 ------------------- 2x + 3y = 2 -2x - 12y = -8 (result of multiplying by -2) ----------------add -9y = -6 y = -6/-9 y = 2/3 x + 6y = 4 x + 6(2/3) = 4 x + 4 = 4 x = 4 - 4 x = 0 solution is (0, 2/3)

zaraharajli97
2015-11-12 19:30:53

2x + 3y = 2 ---- 1st equation x + 6y = 4  x = 4 - 6y  Substituting value of x in 1st equation; 2(4 - 6y) + 3y = 2 8 - 12y + 3y = 2 - 9y = -6 y = [latex] frac{-6}{-9} = frac{2}{3} [/latex] x = 4 - 6y = [latex]4 - 6* frac{2}{3} = 4 - 2*2 [/latex] = 0 Hence, the value of x is 0 and the value of y is [latex] frac{2}{3} [/latex].

ADD ANSWER